Treating posttraumatic stress disorder with MDMA-assisted psychotherapy: A preliminary meta-analysis and comparison to prolonged exposure therapy. (July 2016) - Amoroso, Timothy; Workman, Michael
Since the wars in Iraq and Afghanistan, posttraumatic stress disorder (PTSD) has become a major area of research and development. The most widely accepted treatment for PTSD is prolonged exposure (PE) therapy, but for many patients it is intolerable or ineffective. ±3, 4-methylenedioxymethamphetamine (MDMA)-assisted psychotherapy (MDMA-AP) has recently re-emerged as a new treatment option, with two clinical trials having been published and both producing promising results. However, these results have yet to be compared to existing treatments. The present paper seeks to bridge this gap in the literature. Often the statistical significance of clinical trials is overemphasized, while the magnitude of the treatment effects is overlooked. The current meta-analysis aims to provide a comparison of the cumulative effect size of the MDMA-AP studies with those of PE. Effect sizes were calculated for primary and secondary outcome measures in the MDMA-AP clinical trials and compared to those of a meta-analysis including several PE clinical trials. It was found that MDMA-AP had larger effect sizes in both clinician-observed outcomes than PE did (Hedges' g =1.17 vs. g =1.08, respectively) and patient self-report outcomes (Hedges' g =0.87 vs. g =0.77, respectively). The dropout rates of PE and MDMA-AP were also compared, revealing that MDMA-AP had a considerably lower percentage of patients dropping out than PE did. These results suggest that MDMA-AP offers a promising treatment for PTSD.